Design and implementation of the Information Repository of the Study Center CAD/CAM at the University of Holguin: technology for the management of scientific production - Reyes Fernández, Nelvis; Rodríguez Fernández, Rosa Margarita; Aguilera García, Luis Orlando; Almaguer Riverón, Carmen; Lahera Macías, Adelaida (Revista General de Información y Documentación, 2017)
The design and implementation of the Information Repository of the CAD/CAM Study Center is presented the one that next to the university library of the campus "Oscar Lucero Moya of the University of Holguín constituted the context of the investigation. It was developed a first stage that had the purpose of diagnosing the knowledge that about the RI presented, both the workers of the study center and those of the university library. To collect the information, the questionnaire (with closed and open questions) was applied as a quantitative technique to the teachers of the study center and structured interviews to the librarians. As a qualitative technique, participant observation was developed, which made it possible to obtain information about the behavior of librarians’ knowledge regarding work on the DSpace platform both before and after the training actions. With the results it was possible to plan and develop a training program for library workers and elements were obtained that were considered to develop the second stage of study in which the repository was designed and implemented. In this stage, the focus group was used as a qualitative technique with the researchers of the study center and also a structured interview. As a result it was defined the structure of the repository, the documentary flow and the roles of the actors, both librarians and teachers. In this way both the platform and human resources were ready to develop the RI that is currently available in http://repositorio.uho.edu.cu/jspui/.